(untitled) (Eurasian Journal of Religious Studies, 2017)
Defining the role of islam in soсial development of arab countries – extensive independent problem, which is important in modern life conditions. Arab-muslim world with its long history and culture impregnated with complex and not balanced systems of co-operation of many factors: religious, political, economic, social, ethnic. The ambiguity and inconsistency of different development models in the Arab States was often confirmed by the practice of the last decades. Secularist tendencies, the penetration of Western ideas and values in the public life of Arab countries in the Middle East and North Africa combined with the increasing influence of traditional concepts, the revitalization of religious-political opposition in the countries of study region. The possibility of the dominance of certain political attitudes are largely determined not only by external influences, this category of “third world” countries, the domestic climate, but still powerful influence of the Muslim religion. Turn to Islam and the supporters of a secular way of development, insisting on the need to adapt religious observance to changing domestic and world situation. Islamization of various areas of social and political life, the relationship of religion with the political culture of the Arab and other Muslim countries was widely observed in previous periods of development, and in the last two decades.